A high-resolution hydrogen isotope record of behenic acid for the past 16 kyr in the northeastern United States. (25th August 2017) - Gao, Li; Huang, Yongsong; Shuman, Bryan; Oswald, W. Wyatt; Foster, David
Abstract: D/H ratios of leaf lipids from lacustrine aquatic macrophytes have been shown to record precipitation δD values, which can reflect precipitation-weighted mean annual temperature (MAT) in the northeastern United States. Here we report a high-resolution hydrogen isotopic record from Little Pond, Massachusetts, USA, which we compare with other paleoclimate data from the region, including a similar δD record from Blood Pond, Massachusetts. Together the two datasets provide a >16 ka record of δD variability in the region, affording new insights into Holocene climate history. First, the long-term trends in δD correlate significantly with regional temperatures inferred from alkenone records from nearby areas of the North Atlantic and lake-level inferred changes in precipitation and evaporation. The long-term δD trends reflect a period of maximum regional warmth at ca. 8–6 ka after the collapse of the Laurentide Ice Sheet. Second, unlike the positive relationship between temperature and δD observed over the long-term and during early events like the Younger Dryas, we find that a series of warm and dry events at 4.9–4.6, 4.2–3.9, 2.9–2.1, and 1.3–1.2 cal kya BP coincide with negative δD excursions from the long trends. These events were likely driven by summer drought dynamics.